University-Industry Collaboration Through Engineering Final Year Project - Alhamrouni, Ibrahim; Saad, Mohammad Azannee; Kamarudin, Norida; Hack, Iskandar (2016)
Many studies within the area of engineering education and industrial partnership have highlighted the importance of university-industry collaboration. However, most studies have focused on making or strengthening the collaboration through research works between academicians and professionals that may have placed engineering students in less contributing position. This can lead to a significant amount of loss considering students’ exposure to industry while in their academic years can provide them and future employers with greater benefits. In this paper, we discuss how engineering final year project (EFYP) undertaken by students can be employed to strengthen university-industry collaboration and at the same time, comprehensively prepare students prior to joining the industry. Data for this study were responses obtained through semi-structured interview from two respondents selected through purposive sampling technique.